How tradition and innovation echoes in Jorge de Henin’s memorial - Avelar, Ana Paula (2021)
This chapter aims to demonstrate how in the Description of the Kingdoms of Morocco (1603-1613): Memorial of Jorge de Henin, the author innovates using tradition history and memory concepts. While portraying the Europe of the late 16th century and early 17th century, we outline a brief biography of Jorge de Henin, of his sojourn in Ottoman and Moroccan lands, and his career under the Spanish crown. Through paradigmatic examples, we unfold tradition and innovation in the writing and drawing of the history of Morocco’s kingdoms between 1603-1613, given its reformist ideal. In his memorial, the author advocated using force by the Spanish empire in Moroccan space, arguing that it would reinforce an ideal of an empire whose unity would be achieved by a new universalism, grounded in a single Christian and European civilization.